Genome sequences of three Aegilops species of the section Sitopsis reveal phylogenetic relationships and provide resources for wheat improvement. (12th February 2022) - Avni, Raz; Lux, Thomas; Minz‐Dub, Anna; Millet, Eitan; Sela, Hanan; Distelfeld, Assaf; Deek, Jasline; Yu, Guotai; Steuernagel, Burkhard; Pozniak, Curtis; Ens, Jennifer; Gundlach, Heidrun; et al.
SUMMARY: Aegilops is a close relative of wheat ( Triticum  spp.), and Aegilops species in the section Sitopsis represent a rich reservoir of genetic diversity for the improvement of wheat. To understand their diversity and advance their utilization, we produced whole‐genome assemblies of Aegilops longissima and Aegilops speltoides . Whole‐genome comparative analysis, along with the recently sequenced Aegilops sharonensis genome, showed that the Ae. longissima and Ae. sharonensis genomes are highly similar and are most closely related to the wheat D subgenome. By contrast, the Ae. speltoides genome is more closely related to the B subgenome. Haplotype block analysis supported the idea that Ae. speltoides genome is closest to the wheat B subgenome, and highlighted variable and similar genomic regions between the three Aegilops species and wheat. Genome‐wide analysis of nucleotide‐binding leucine‐rich repeat ( NLR ) genes revealed species‐specific and lineage‐specific NLR genes and variants, demonstrating the potential of Aegilops genomes for wheat improvement. Significance Statement: Whole‐genome comparative analysis using de novo assemblies of Aegilops longissima and Aegilops speltoides, along with the recently sequenced Aegilops sharonensis genome, strengthen evolutionary evidence that Ae. longissima and Ae. sharonensis genomes are highly similar and are most closely related to the wheat D subgenome. By contrast, the Ae. speltoides genome is more closely related to the B subgenome. A detailed NLR annotation and haplotype block analysis aims to help further research using these species to improve wheat.